New species of Sericini from Sri Lanka (Coleoptera, Scarabaeidae) - Ranasinghe, Sasanka; Eberle, Jonas; Benjamin, Sresh P.; Ahrens, Dirk (European Journal of Taxonomy, 2020)
In a recent project, extensive fieldwork was carried out in several parts of Sri Lanka to investigate scarab biodiversity. Here we present the first results of this survey and describe four new Sericini species: Selaserica athukoralai sp. nov., Neoserica dharmapriyai sp. nov., Maladera cervicornis sp. nov., M. galdaththana sp. nov. Further, new locality records for 20 already known species are given. The genitalia and the habitus of all new species are illustrated and photos of the habitats of the new species are given.